Clinico-bacteriological profile and antibiotic sensitivity pattern in pyodermas: A Hospital Based Study - U Paudel; S Parajuli; DB Pokhrel (Nepal Journal of Dermatology, Venereology & Leprology)
DOI: http://dx.doi.org/10.3126/njdvl.v11i1.7935